Muscle architecture of the medial gastrocnemius during growth - Yasuyoshi Mogi (Journal of Physiological Anthropology)
Abstract Background Muscle architecture is closely related to muscle function. Increased knowledge of growth changes in muscle architecture will provide insights into the development of human movements and sports performance during the growth period. However, it is unclear how the muscle architecture of the medial gastrocnemius (MG) grows. This study examined the effects of growth on the muscle architecture of MG. Methods The brightness-mode ultrasonography technique was used to measure the muscle thickness, pennation angle, and fascicle length of MG in 146 Japanese boys aged to 6.2 − 17.9 years. The relative muscle thickness was calculated by dividing the absolute muscle thickness by body mass1/3. The years from the age at peak height velocity were estimated for each participant, and used as the maturity index. A simple regression analysis was performed for the two variables in the full age range, as well as separately for the 5 − 12 years and 12 − 19 years subgroups. Results and conclusion The maturity index and chronological age were positively correlated with the relative muscle thickness, pennation angle, and fascicle length of MG. Subgroup analyses showed that chronological age was significantly correlated with the pennation angle, fascicle length, and absolute muscle thickness, except for the pennation angle of the 5 − 12 years subgroup. The present results indicate that muscle hypertrophy and elongation of fascicle length occur with growth. Our findings also suggest that the growth changes in pennation angle of MG differ between pre-adolescence and adolescence.